Protostars and Planets VI 2014
DOI: 10.2458/azu_uapress_9780816531240-ch003
|View full text |Cite
|
Sign up to set email alerts
|

The Origin and Universality of the Stellar Initial Mass Function

Abstract: We review current theories for the origin of the Stellar Initial Mass Function (IMF) with particular focus on the extent to which the IMF can be considered universal across various environments. To place the issue in an observational context, we summarize the techniques used to determine the IMF for different stellar populations, the uncertainties affecting the results, and the evidence for systematic departures from universality under extreme circumstances. We next consider theories for the formation of prest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
122
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 103 publications
(191 reference statements)
5
122
0
Order By: Relevance
“…we consider it to be real, as the onset of the flattening occurs at ∼ 0.2 M ⊙ , significantly above our 80 percent completeness limit of 0.051 M ⊙ , and because the flattening is consistent with both the expected behaviour of the low-mass core mass function (e.g. Chabrier 2003;Offner et al 2014) and the observed behaviour of the core mass function determined in previous studies of Ophiuchus (MAN98; S08).…”
Section: Source Mass Distributionsupporting
confidence: 48%
See 2 more Smart Citations
“…we consider it to be real, as the onset of the flattening occurs at ∼ 0.2 M ⊙ , significantly above our 80 percent completeness limit of 0.051 M ⊙ , and because the flattening is consistent with both the expected behaviour of the low-mass core mass function (e.g. Chabrier 2003;Offner et al 2014) and the observed behaviour of the core mass function determined in previous studies of Ophiuchus (MAN98; S08).…”
Section: Source Mass Distributionsupporting
confidence: 48%
“…The mass at which the CMF turns over is typically ∼ 3 times that of the IMF, suggesting that, if there is a direct link between the CMF and the IMF, the process of conversion of a prestellar core into a main-sequence star is ∼ 33% efficient (Offner et al 2014).…”
Section: The Initial Mass Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of the stellar initial mass function (IMF) is one of the outstanding problems in contemporary theoretical astrophysics (Krumholz 2014;Offner et al 2014). The observed IMF displays a characteristic peak at ∼ 0.2 − 0.3 M , with a decline in the number of objects on either side of this plateau (Kroupa 2002;Chabrier 2003Chabrier , 2005Bastian, Covey & Meyer 2010;Parravano, McKee & Hollenbach 2011;Offner et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The observed IMF displays a characteristic peak at ∼ 0.2 − 0.3 M , with a decline in the number of objects on either side of this plateau (Kroupa 2002;Chabrier 2003Chabrier , 2005Bastian, Covey & Meyer 2010;Parravano, McKee & Hollenbach 2011;Offner et al 2014). This peak appears to be universal or nearly so within the Milky Way, and even in the most extreme environments to which we have access its location is different by at most a factor of ∼ 2 − 3 (e.g., van Dokkum & Conroy 2010, mark.krumholz@anu.edu.au 2011; Cappellari et al 2012;Spiniello et al 2012Spiniello et al , 2015Conroy et al 2013).…”
Section: Introductionmentioning
confidence: 99%